Frequency of Arrhythmia after Acute Myocardial Infarction During Admission to the Coronary Care Unit in Ad_diwaniyah Teaching Hospital - Radhi F. Shlash1, Sarah Abdul Kareem Abdul Jabbar1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Aims of the Study: ]To study the incidence of arrhythmias after Acute Myocardial Infarction (AMI) with respect to type of arrhythmia, risk factors , age and sex distribution, and location of infarction in a sample of patients during their admission in the coronary care unit in Ad Diwaniyah teaching hospital.Patients and Method : This is a cross sectional study involving a cohort of 97 Iraqi patients diagnosed with acute myocardial infarction and admitted to the coronary care unit of Ad Diwaniyah teaching hospital in Ad Diwaniyah governorate / Iraq . All patients who admitted in the ccu for the period from January 2019 to july 2019 were followed by ECG records for any arrhythmia detected.Result : Out of 97 patients diagnosed with AMI, 61 patients (62.88%) developed one type or more of arrhythmia, including 35 male (57.3%) and 26 female (42.6%), with the highest incidence (40.98%) above 70 years of age .Reviewing the main risk factors in the past Medical History of those patients : hypertention was the most significant with 39 hypertensive patients (63.93%) .The types of arrhythmias found in the patients included in this study were 27 cases with Premature Ventricular Contraction (27.8% of all patients with AML), 13 cases of Atrial Fibrillation (13.4%), 18 cases of Sinus Tachycardia (18.5%), 7 cases of premature Atrial Contraction (7.2%) , 6 cases of Ventricular Tachycardia (6.2%) , 3 cases with Ventricular Fibrillation (3.09%), 3 cases of Sinus Bradycardia (3.09%), 5 cases with accelerated junctional rhythm (5.1% ) , 3 cases of first degree A-V Block (3.09%), 2 cases with Complete Heart Block (2.06%) , 7 cases of Right Bundle Branch Block (7.2%) and 5 cases with Left Bundle Branch Block (5.11%).